Continuous fixed-bed oxidation of metronidazole by the sulfate radical based process over nitric acid treated granular activated carbon. (August 2020) - Forouzesh, Mojtaba; Ebadi, Amanollah; Aghaeinejad-Meybodi, Abbas
Abstract: Activation of persulfate in the presence of nitric acid treated granular activated carbon was studied in order to investigate the degradation of metronidazole from aqueous medium in the continuous up-flow fixed-bed reactor. A tubular glass reactor with internal diameter of 2 cm and height of 15 cm was filled with desirable mass of rod shaped activated carbon with diameter of 4 mm and height of 6 mm. The synthetic wastewater containing persulfate and metronidazole was entered into the reactor in up-flow operation. At steady state condition and under the optimum values of operating parameters, about 88 % of influent persulfate was decomposed and decreased to 73 % after 7 h. Under this condition, the metronidazole removal reached to 93 % and gradually decreased to 74 % at the end of process due to the saturation of the catalyst and occupation of available active sites for sulfate radical production. The results indicated promising performance of sulfate radical based advanced oxidation process in continuous fixed-bed reactor for degradation of resistant pollutants from aqueous medium.